The Search for Thermonuclear Transients from the Tidal Disruption of a White Dwarf by an Intermediate-mass Black Hole - Sebastian Gomez; Suvi Gezari (The Astrophysical Journal, 2023)
The close encounter of a white dwarf (WD) with a black hole (BH) could result in the tidal disruption of the WD. During this encounter, the WD can undergo a thermonuclear explosion due to its tidal compression, resulting in an optical transient similar to a Type Ia supernova, hereafter a Ia-TDE. Nevertheless, this will only be physically observable if the BH is ≲10 ^5 M _⊙ . Finding a Ia-TDE would therefore imply the discovery of an intermediate-mass BH (IMBH) ≲10 ^5 M _⊙ . Here, we search the entire Zwicky Transient Facility alert stream for these elusive Ia-TDEs. We restrict our search to nuclear transients in dwarf galaxies, the likely sites for IMBHs, and find a total of six possible nuclear Ia-TDE candidates. We find SN 2020lrt to be the most likely Ia-TDE candidate, thanks to its strong resemblance to light-curve and spectroscopic models of Ia-TDEs. We measure the stellar masses of the dwarf galaxies hosting these transients to be ≲10 ^9 M _⊙ ; if confirmed to harbor BHs, these would prove the existence of IMBHs in some of the lowest-mass galaxies known. Additionally, we searched for off-nuclear Ia-TDEs, but were unable to find more robust candidates in the outskirts of galaxies than in their nuclei. This supports the hypothesis that the nuclear Ia-TDE candidates are WDs tidally compressed by IMBHs in the cores of galaxies, as opposed to a class of transient that can occur anywhere in a galaxy. We have laid the groundwork to systematically search for Ia-TDE candidates in existing and future time-domain surveys. The rapid characterization of their nature will result in not only the confirmation of a Ia-TDE, but also the unambiguous discovery of bona fide IMBHs.